The 40k used as tracer of Saharan dust contributions. - Pérez-Martínez, Manuel; Dueñas-Buey, Mª Concepción; Cañete-Hidalgo, Sergio Andrés; Gordo Puertas, Elisa; Cabello Ganuza, María; Liger-Pérez, Esperanza (My University, 2018)
The present study is carried out in Málaga, frequently affected by intrusions of air masses with high concentrations of atmospheric particulate matter. 40K is a natural radionuclide and has been associated with the arrival of coarse re-suspended material from the Africa continent. A systematic 13-year analysis (January 2005-December 2017) of the concentration of radionuclides in bulk (wet + dry) deposition and PM10 air concentrations has been performed to test the possible utility of 40K as tracer of African mineral dust inputs in Málaga (4° 28ʹ 8ʺ W ;36° 43ʹ 40ʺ N). Also the atmospheric aerosols are collected using a high volume sampler during 9-year (January 2009-December 2017). It is a prerequisite to know the environmental long-term behaviour of radionuclides an a relatively large number of values are required for statistically meaningful conclusions . The identification of African dust events was carried by 96-hour back-trajectory analysis arriving at thee different heights (500 m, 1500m, 3000m a.g.l.) calculate with the HYSPLIT model , and by the information obtained from the output of the dust regional Atmospheric model (DREAM 8b).
Keywords: Aerosoles atmosféricos; 40K; Natural radionuclide; Aerosols